MANUAL THERAPY IN THE FIBROMYALGIA TREATMENT (Fiep Bulletin - online, 2014)
The present research shows the treatment of fibromyalgia using the techniques of the physical therapy. It's a case research with a female patient who has fibromyalgia. The data were collected through clinical history, in which the patient related her symptoms, and through physical examination, in which the tender points were found. Twenty manual therapy sessions were held through myofascial techniques, besides the stretch exercises, relaxing and ultra-sound in the tender points to help in the patient's treatment. In order to measure the patient's pain level, a pain visual analogue scale was used in the 1st, 5th, 10th, 15th and 20th sessions. It's been observed that, the manual therapy treatment had an important result in the reduction of the symptoms impact of fibromyalgia in the patient's life, improving her functional capacity and contributing to maintain her quality of life.
Keywords: fibromyalgia; physical therapy; treatment